Pilvipalveluiden tietoturvallisuus ja sen vaikutukset käyttäjien toimintaan - Erola, Olli-Pekka (2018)
The aim of this study was to find out what kind of challenges are connected to the information security of cloud computing. The advantages of cloud computing are highly identified and now the challenges are getting more and more attention. The aim of this study was to take a closer look of how the commonly known challenges are affecting users behavior with cloud computing. The challenges of information security were limited to the SaaS-layer challenges, because that is the layer that users are dealing with. This study was based on a literature review. Based on that literature review, some deductions were made for the empirical part of the study. The empirical part was executed by qualitative interviews, which were held among cloud computing users. The questions for the interviews were based on the literature review. Because of that it was possible to compare the answers of the empirical part to the conclusions made from the literature review. The answers from the interviews were decoded by finding similar things between them. Because of the decoding it was easier to compare answers between each other. The main findings concerning the information security of SaaS-services were the many problems of data security. In addition to that challenges were found from the security of applications and network, access controlling and requirements of availability and the challenges that comes with it. All these together are limiting the way that cloud computing users are using the services. Users are not willing to give all their information to cloud services because they feel that the level of information security is not high enough. Users also feel that they are able to affect quite little to the information security. Service providers are carrying the biggest responsibility of information security. The only way that users felt they could affect the level of information security was to control which kind of data they are moving to the cloud. The main conclusion of this study was that the challenges related to the information security of cloud computing are limiting the way that users are using them. Users are not ready to give away all of their information to the service provider. That’s why they are controlling which kind of data they are moving to the cloud.